The Call of the proper nouns in the Quran (Rhetorical Study) - Abdelrahman Moawad Ali Tahawi (IJAS: Indonesian Journal of Arabic Studies, 2021)
This research contains three objectives, the first of which is to extrapolate the positions of the call of the flags that are mentioned in the Qur’anic verses and to form a clear picture of this type of call with the analysis of a number of Qur’anic evidence rhetorically. The second is to follow what the rhetoricians dealt with regarding directing the discourse in the style of the appeal, and the use of the forms of the appeal in a way other than its original meaning. The third is to monitor the overall relationship between the question and the Qur’anic call and the significance of this relationship. In writing this research, the researcher followed the inductive and analytical approaches by extrapolating and tracing the texts and then analyzing them rhetorically. The research concluded with several results, including: (1) The Noble Qur'an has numerous references to the call to science, therefore it is an honor for the herald in some cases and a mocking in others. (2) In many places, the Qur'anic verses adopted the method of calling, which is one of the methods of preparation and educational preparation that leads to attracting the caller's attention and urging him to approach and focus, as well as creating a sense of familiarity, grooming, and privacy that makes him feel how important it is, and the interest of the Qur'anic discourse in it makes him more ready to receive and comply.  (3) The frequent occurrence of command, prohibition, and interrogation construction methods associated with the Qur'anic call, as well as their occurrence in the Holy text, is frequently accompanied by a semantic shift in which these methods separate their direct literal significance from other indications, which is known in the old rhetorical lesson as the idea of purposes. This change from literal to rhetorical meaning implies a unique capacity that aids in drawing the recipient's attention and maintaining his communication with the text at its most responsive and interactive level. يحتوي هذا البحث على ثلاثة أهداف، أولها استقراء مواضع نداء الأعلام التي وردت في السور القرآنية وتكوين صورة واضحة لهذا النمط  من أنماط النداء مع تحليل عدد من الشواهد القرآنية تحليلا بلاغيا. ثانيها تتبع ما تناوله البلاغيون بشأن توجيه الخطاب في أسلوب النداء، واستعمال صيغ النداء في غير معناه الأصلي. ثالثها رصد العلاقة الجامعة بين الاستفهام والنداء القرآني ومعزى هذه العلاقة. واتبع الباحث في كتابة هذا البحث المنهجين الاستقرائي والتحليلي وذلك باستقراء وتتبع النصوص ثم تحليلها بلاغيا. وقد خلص البحث إلى عدة نتائج منها: (1) تتعدد دلالات النداء بالعلمية في القرآن الكريم فتكون في بعض الشواهد تشريفا للمنادى وتكون سخرية منه في بعضها الآخر.(2) اعتمدت السور القرآنية أسلوب النداء في مواضع كثيرة وهو أحد أساليب التوطئة والتهيئة التربوية التي تؤدي إلى جذب انتباه المنادي وحثه على الاقتراب والتركيز وإيجاد نوع من الألفة والاستمالة والخصوصية التي تشعره بمدى أهميته واهتمام الخطاب القرآني به  يجعله أكثر استعدادا للتلقي والامتثال. (3) كثرة ورود الأساليب الإنشائية من أمر ونهي واستفهام مقترنة مع النداء القرآني وكثيراً ما يكون ورودها في النص الكريم مصحوبا بتحول دلالي تفارق فيه هذه الأساليب دلالتها الحرفية المباشرة إلى دلالات أُخر وهو ما يعرف في الدرس البلاغي القديم بفكرة الأغراض. وهذا التحول من الدلالة الحرفية المباشرة إلى الدلالة البلاغية ينطوي على قدرة لافتة تسهم في جذب انتباه المتلقي وبقاء تواصله مع النص في أكثر حالاته تجاوبا وتفاعلا.